An analysis of the determinants behind having an additional job by employees - Wioletta Grzenda (Economic and Environmental Studies (E&ES), 2018)
Apart from having the main job, many people in Poland decide to take additional jobs. There are many potential factors which determine having a second job. These include varied needs of individuals, such as the desire to improve their material status, family situation, or the opportunities arising from human capital. In this study, apart from the aforementioned needs, the features of individuals, such as age, sex, place of residence and the features of the main workplace have been included. Unfortunately, some determinants of the studied phenomenon cannot be clearly observed or are generally unobservable. Hence, the models with unobservable heterogeneity, which were used in this study, are of particular importance in modelling this type of phenomena. The purpose of this paper was to show the demographic profile of a two-job worker. This has been done by the assessment of the impact of selected determinants on having an additional job. Furthermore, the scale of the impact of the studied determinants has been compared in the case of women and men. The study used the Bayesian logistic regression model.
Keywords: J60; J29; 330; additional job; logistic regression; Bayesian inference